The Use of TQM as A Model to Improve University Performance in Indonesia - Burhanuddin, Burhanuddin; Supriyanto, Achmad (Faculty of Education Universitas Negeri Malang, 2018)
The purpose of this study is to assess higher education performance in Indonesia, and how TQM is used as a model to promote this sector. The investigation was conducted employing a meta-analysis technique. Literatures and findings from some studies were reviewed to explore the performance indicators and how these were improved employing this model. Results identified unsatisfied universities performance and its development still moved slowly. Insufficient governance was found as one of factors influencing this condition. Future studies are needed to discover broader insights about appropriate models in improving the performance.Keywords: university, management, TQM, improvement, teaching and learning